Pien-Tze-Huang protects cerebral ischemic injury by inhibiting neuronal apoptosis in acute ischemic stroke rats. (12th June 2018) - Zhang, Xiaoqin; Zhang, Yiping; Tang, Songqi; Yu, Lishuang; Zhao, Youqin; Ren, Qiangqiang; Huang, Xiaoqiang; Xu, Wen; Huang, Mingqing; Peng, Jun
Abstract: Ethnopharmacological relevance: Pien-Tze-Huang (PZH) is a famous formula of traditional Chinese medicine used to treating stroke. However, the protective effect of PZH and its mechanisms in acute ischemic stroke remain to be explored. Aim of the study: To investigate the protective effect of PZH on neuronal apoptosis in acute cerebral ischemic injury rats and explore its underlying mechanisms. Materials and methods: The effects of PZH were studied in acute ischemic stroke rats induced by transient middle cerebral artery occlusion, and the mitochondria-mediated apoptotic proteins including cytochrome C (Cyt C), Bax, Bcl-xl, P53, caspase-3, and caspase-9 as well as AKT and glycogen synthase kinase-3 beta (GSK-3β) were assessed. Results: Four days of PZH treatment (180 mg/kg) could significantly reduce cerebral infarct volume, improve neurological deficit, attenuate inflammatory response, and inhibit neuronal apoptosis in acute ischemic stroke rats. Moreover, PZH treatment significantly decreased cytosolic Cyt C, Bax, P53, cleaved caspase-3, and cleaved caspase-9 levels, but elevated mitochondrial Cyt C and Bcl-xl levels. PZH treatment also increased phosphorylation of AKT and GSK-3β. Conclusion: PZH potently protects the brain from cerebral ischemia/reperfusion injury in vivo, and inhibiting mitochondria-mediated neuronal apoptosis as well as attenuating inflammatory responses may be involved in this effect. This study provides experimental basis of PZH in treating acute cerebral ischemic stroke, which would provide some novel insights for its prevention and treatment of ischemic stroke. Graphical abstract: fx1